Breaking down the success barrier: The mediating role of absorptive capacity in linking entrepreneurial orientation to IT project success - Sundas Khan; Sabeen Hussain Bhatti; Umer Zaman; Maqsooda Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
A pragmatic approach to business innovation is to bridge transformational entrepreneurship with the management of innovation-based projects. However, scholars have given limited attention to the underlying factors that explain linkages between entrepreneurial orientation and project success. Moreover, the lack of absorptive capacity touch points, limits the organizational potential to cope with innovation-based project challenges. Hence, the study purpose is to investigate the impact of entrepreneurial orientation (EO) on IT project success, under mediating conditions of absorptive capacity (ACAP). The study employed a deductive approach to empirically test the conceptualized model using partial least squares technique for structural equation modeling, involving surveyed data of IT professionals. The results confirm the significantly positive effect of EO on IT project success. The findings further verify that ACAP partially mediates the EO relationship with IT project success. Frommanagerial perspective, the study highlights the importance of aligning project management practiceswith organization's entrepreneurial orientation thatempowers organizational membersto maximize on successful project outcomes with the timely consumption and application of new knowledge.
Keywords: 330; entrepreneurial orientation; innovation; absorptive capacity; information technology project success; IT industry